On Vietnamese representatives of the ant spider genus Heradion (Araneae: Zodariidae) - Chami-Kranon, Thanaphum; Ono, Hirotsugu (Zootaxa, 2007)
A new species of the genus Heradion Dankittipakul & Jocqué, H. intermedium spec. nov., is described based on specimens collected in southern Vietnam. Heradion paradiseum (Ono) comb. nov., H. flammeum (Ono) comb. nov. and H. momoinum (Ono) comb. nov. are here transferred from Mallinella Strand. All the Heradion species treated in the present study belong to the H. naiadis-group which comprises six nominal species known from evergreen hill forests of Thailand and Vietnam. A map showing distribution of the species-group and a key to species of the genus Heradion of Vietnam are provided.